Strategi Manajerial dalam Upaya Mempertahankan Retensi Dokter Spesialis: Studi Kualitatif di Rumah Sakit Islam Pati - Muhammad Rizal Fauzi; Purwadhi Purwadhi; Yani Restiani Widjaja (Kawanad : Jurnal Pengabdian kepada Masyarakat, 2026)
In Indonesia, a critical issue facing the healthcare system today is the low availability of specialist doctors that serve regional hospitals while other areas have reported a physician-to-population ratio phase below the Indonesian national ideal. This study aims to prove the effect of intrinsic and extrinsic factors on specialist doctor retention in RSI Pati, a private Islamic hospital located in Central Java, Indonesia, where increasing numbers of specialists resigned after 2025. A qualitative case study design was used, and data were collected by conducting in-depth interviews with 11 participants from four occupational groups: active specialist doctors, former specialist doctors, and hospital managers. The results were further synthesized along a SWOT–Canvas framework to orient both internal and external factors to operational managerial activities. Loyalty of Doctors is determined by various Aspects and Interdependent factors such as clear and regular remuneration programs, Islamic culture in the organization that allows colleague-ship among doctors, supportive work environment (with HR-is appropriate accommodation) along with medical amenities eg. HMIS etc., career development opportunities etc. Based on these results, a range of managerial strategies was constructed including: rationalization of incentive schemes; strengthening human resource management systems; developing value-oriented professional services and expanding referral networks. These methods aim to ensure the long-term and competitive retention of specialist doctors in RSI Pati.